The Banking Industry in Morocco: Evolution, Challenges, and Opportunities in a Changing Global Context - (:unkn) unknown (My University, 2025)
The Moroccan banking sector is undergoing a major transformation due to regulatory reforms, digitization and regional expansion. In fact, thanks to gradual modernization, it has strengthened its financial stability and consolidated its presence in sub-Saharan Africa, thus affirming its strategic role in financing the economy.However, several challenges remain. On the one hand, financial inclusion remains limited, hindering access to banking services for part of the population. On the other hand, stricter regulatory requirements impose increased compliance on financial institutions, impacting their agility. Moreover, although digitalization is progressing, its integration remains incomplete, limiting gains in efficiency and innovation.Nevertheless, these constraints are opening the way to new opportunities. The rise of fintech, the adoption of ESG criteria and the acceleration of digital transformation are strategic levers for improving the sector's competitiveness. In this context, this article examines, through an in-depth review of academic literature and institutional reports, the current dynamics of the Moroccan banking sector and proposes recommendations aimed at strengthening its resilience and fully seizing the opportunities of achanging market.
Keywords: African Research